Mexico : Arrangement Under the Flexible Credit Line and Cancellation of the Current Arrangement. (IMF Staff Country Reports; Country Report ;, 2011)
Strong economic fundamentals, robust policy framework, and a sustained track record of excellent policy implementation have facilitated the maintenance of orderly economic conditions in Mexico even amidst the substantial external volatility during the global crisis. Executive Directors welcomed the authorities' commitment to maintain Mexico's strong policy frameworks and take needed actions to manage unforeseen risks. The arrangement of contingent financing with the IMF through the Flexible Credit Line has helped Mexico to maintain confidence and also to insure against external risks while supporting a macroeconomic strategy.